2014
DOI: 10.1186/1471-2474-15-78
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of the Norwegian version of the Disabilities of the Arm, Shoulder and Hand questionnaire in patients with shoulder impingement syndrome

Abstract: BackgroundPatient-rated outcome measures (PROMs) are an important part of clinical decision-making in rehabilitation of patients with shoulder pain. The Disabilities of Arm, Shoulder and Hand (DASH) questionnaire was designed to measure physical disability and symptoms in patients with musculoskeletal disorders of the upper extremity and is one the most commonly used outcome measures for patients with shoulder pain. The purpose of this study was to investigate the reliability and validity of the Norwegian vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
1
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 51 publications
0
35
1
2
Order By: Relevance
“…Missing items were imputed as the average of the remaining items [17]. A previous study based on the same sample of patients demonstrated acceptable test-retest reliability, internal consistency and construct validity of the Norwegian version of the DASH [18]. …”
Section: Methodsmentioning
confidence: 99%
“…Missing items were imputed as the average of the remaining items [17]. A previous study based on the same sample of patients demonstrated acceptable test-retest reliability, internal consistency and construct validity of the Norwegian version of the DASH [18]. …”
Section: Methodsmentioning
confidence: 99%
“…практически все пациенты заполнили шкалу в течение 5 мин. конструктная валидность шкалы оБп, определяемая при расчете коэффициента альфа кронбаха, показала, что сокращенная версия шкалы оБп является однородной по структуре вопросов для диагностики сИс, наравне с aSeS (альфа кронбаха aSeS в испанской версии -0,91, в финской версии aSeS -0,88 (95% дИ 0,84 to 0,91) [23,24] и сопоставимой со шкалой daSH, альфа кронбаха daSH в норвежской версии -0,93 [25].…”
Section: Discussionunclassified
“…для этих целей применяют однотипные тесты-опросники с высокой воспро-изводимостью. воспроизводимость шкалы aSeS в переводных версиях составляет: Icc -0,83 (95% дИ 0,70-0,90) [24], воспроизводимость daSH в переводной версии: Icc -0,89 [25]. по данным анализа ретестовой надежности, проводимой у 60 пациентов в нашем исследовании, внутриклассовый коэффициент корреляции Icc полной версии шкалы оБп составил 0,98 (95% дИ 0,98-0,99), что означает очень высокую надежность теста.…”
Section: Discussionunclassified
“…Most studies that applied the DASH scale used the unifactorial structure 3,14,[34][35][36][37] proposed by the authors. 7,28 In this study, the unifactorial structure could not be adjusted for the Brazilian and American samples, even after refining.…”
Section: Commentmentioning
confidence: 99%